The realization of a wide-angle voice transmission non-line-of-sight ultraviolet communication system. (September 2021) - Deng, Yangyang; Wang, Yuehui; Zhang, Yiqing; Du, Axin; Liu, Jianguo
Abstract: A 300 kbps wide-angle non-line-of-sight ultraviolet communication system with voice transmission function is designed here. Based on Poisson distribution theory, we design the symbol detecting method for the receiving discrete photon signals. Using 272 nm LED array as the light source and PMT as the detector, the voice transceiver is integrated into the carriable size of 200 × 90 × 65 mm 3 . An outfield test shows the system obtains the BER of 0.88% under 200 m. Under 10° wide-angle deviation of the transmitter, a BER below 1.33% is achieved.